2019
DOI: 10.1002/gps.5219
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and interventional implications of telemedicine in Alzheimer's disease and mild cognitive impairment: A literature review

Abstract: Introduction Worldwide, life expectancy, and aging‐related disorders as mild cognitive impairment (MCI) and Alzheimer disease (AD) are increasing, having a rising impact on patients' quality of life and caregivers' distress. Telemedicine offers many possibilities, such as remote diagnosing and monitoring of patients. Objective The purpose of this study is to provide a narrative synthesis of the literature about the implementation of telemedicine for diagnosis, treatment, and follow‐up of patients with AD and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 95 publications
0
48
0
Order By: Relevance
“…Clinical management of cognitive disorders (ie, managing medical and cognitive problems at home)—for example , educate/assist caregivers in monitoring simple vital signs such as blood pressure, pulse, temperature, blood glucose test, and/or oxygen saturation at home; blood pressure monitoring may be particularly important in limiting further vascular contributions to dementia; oxygen saturation may detect desaturation due to pneumonia/COVID‐19 secure arrangement for medical consultation (via telephone or telemedicine) with general practitioners/specialists to maintain patient care; doctors could make home visits if deemed necessary, but they need to follow infection control measures and put on proper PPE for home visits specialist clinics should triage patients for priority assessment, including assessment of new referrals, 67,68 in particular for those with severe behavioral problems, rapidly progressive cognitive decline, young onset dementia, suspected cases of reversible dementia, or high caregivers’ burden administer cognitive assessment as part of the consultation via telemedicine; 68‐71 note however that the standard norms derived from traditional face‐to‐face assessment may not apply to on‐line assessment 69 conduct simple cognitive assessments (eg, Montreal Cognitive Assessment 5‐minute version) via telephone, 71,72 although there may be challenges, for example, in very impaired or deaf patients consider computerized or online cognitive self‐assessment programs; 73,74 note however that not all versions have been validated 74 remind patients/caregivers to refill and be compliant to prescribed medications; pharmacies should facilitate repeat prescriptions and help coordinate home delivery of medication where relatives are unavailable discuss in advance patients’ and caregivers’ wishes with respect to receiving life‐sustaining treatment including hospitalization, resuscitation, and ventilatory support in the event of respiratory failure due to COVID‐19; ideally, palliative care services should be available in the community 75 use various home sensors in capturing a wide range of health parameters (eg, blood pressure, pulse, temperature, oxygen saturation, heart rhythm, movement, performance in activities of daily living) if such technologies are available 76 …”
Section: Community Home‐based Care Strategiesmentioning
confidence: 99%
“…Clinical management of cognitive disorders (ie, managing medical and cognitive problems at home)—for example , educate/assist caregivers in monitoring simple vital signs such as blood pressure, pulse, temperature, blood glucose test, and/or oxygen saturation at home; blood pressure monitoring may be particularly important in limiting further vascular contributions to dementia; oxygen saturation may detect desaturation due to pneumonia/COVID‐19 secure arrangement for medical consultation (via telephone or telemedicine) with general practitioners/specialists to maintain patient care; doctors could make home visits if deemed necessary, but they need to follow infection control measures and put on proper PPE for home visits specialist clinics should triage patients for priority assessment, including assessment of new referrals, 67,68 in particular for those with severe behavioral problems, rapidly progressive cognitive decline, young onset dementia, suspected cases of reversible dementia, or high caregivers’ burden administer cognitive assessment as part of the consultation via telemedicine; 68‐71 note however that the standard norms derived from traditional face‐to‐face assessment may not apply to on‐line assessment 69 conduct simple cognitive assessments (eg, Montreal Cognitive Assessment 5‐minute version) via telephone, 71,72 although there may be challenges, for example, in very impaired or deaf patients consider computerized or online cognitive self‐assessment programs; 73,74 note however that not all versions have been validated 74 remind patients/caregivers to refill and be compliant to prescribed medications; pharmacies should facilitate repeat prescriptions and help coordinate home delivery of medication where relatives are unavailable discuss in advance patients’ and caregivers’ wishes with respect to receiving life‐sustaining treatment including hospitalization, resuscitation, and ventilatory support in the event of respiratory failure due to COVID‐19; ideally, palliative care services should be available in the community 75 use various home sensors in capturing a wide range of health parameters (eg, blood pressure, pulse, temperature, oxygen saturation, heart rhythm, movement, performance in activities of daily living) if such technologies are available 76 …”
Section: Community Home‐based Care Strategiesmentioning
confidence: 99%
“…With the continuous development of big data processing, cloud computing, and other emerging data technologies, telemedicine has developed a variety of telemedicine service modes such as teleconsultation, telecardiology, and telemedicine teaching [4]. With the development of data processing and sharing models, more medical service modalities will be developed and applied to social services [5]. Population aging is a product of economic and social development, and as an irreversible objective progress trend, it has become a major crisis faced by human society in the 21 st century [6].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, domains that are difficult to assess over the telephone may be assessed over videoconference such as visuospatial function/construction, praxis, social cognition/emotional processing, and facial recognition. A systematic review of telemedicine studies in AD and MCI demonstrated that there was no difference in the efficacy comparing in‐person diagnosis with diagnosis made via videoconference 61 …”
Section: Remote Cognitive Assessmentsmentioning
confidence: 99%